Anabolic androgenic steroids impact on cardiovascular risk and cardiovascular events. The literature review - Ubysz, Eryk; Kwitowska, Patrycja; Muraszewski, Łukasz; Muraszewska, Emilia; Pyjecka, Małgorzata; Król, Agata; Lewandowska, Edyta; Łuczyński, Cezary; Paczkowski, Maciej; Wręczycki, Mariusz (Quality in Sport, 2026)
Background: Anabolic-androgenic steroids are used as a form of doping. Scientific research shows the association of AAS use with multidirectional effects on the cardiovascular system. Aim: To collect overall information on the effects of AAS on the cardiovascular system based on current scientific studies. Material and methods: The literature available in PubMed and Google Scholar databases was reviewed using the keywords. Results: The results of scientific studies have confirmed the effects of AAS on vascular calcification and the development of atherosclerosis. Studies suggest an increased risk of thromboembolic incidents (lack of general consensus). AAS use is associated with the development of hypertension and left ventricular hypertrophy. Their consequences include impaired cardiac systolic and diastolic function, arrhythmias and susceptibility to ischemia. The use of AAS carries the risk of arrhythmias of ventricular and supraventricular origin. AAS increase the risk of myocardial infarction both in the mechanism of coronary artery stenosis and without significant stenosis. Conclusions: AAS use is associated with increased cardiovascular risk and cardiovascular events. A collective knowledge of the effects of AAS abuse may be useful in the diagnostic and therapeutic process, as well as to develop methods for primary prevention. Some of the effects of AAS use require further research.